PENGARUH PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR YAMAHA PADA PT. GRAHA YAMAHA DI PADANGSIDIMPUAN - FARIZAL, NANDO (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2017)
PT. Yamaha Graha in Padangsidimpuan must be able to compete and optimize performance professionally to achieve maximum profit. Marketing activities are direct efforts to achieve, provide information and persuade consumers to buy and use their products. Some people do not know the advantages possessed by Yamaha products, do not know the types of Yamaha products, do not know the price concept of Yamaha products. Judging from the parking lot, it turns out that Yamaha products are still seldom interested in the City of Padangsidimpuan. This research is a quantitative study using simple regression analysis. Data collection techniques used by researchers in this study were to use questionnaires and through interviews with individuals whose information was needed for completing the data in this study. The sample used in this study were 70 respondents. The test results of the coefficient of determination (R2) can be seen that 28.6 percent of the promotion variables are able to influence purchasing decisions and the remaining 71.4 percent are influenced by other variables not discussed in this study. Based on the results of this study showed a positive and significant effect, namely promotion of the decision to purchase a Yamaha motorcycle in Padangsidimpuan.